Mettertron - Bridging Metadata Repositories and Terminology Servers. - Schladetzky, Jan; Kock-Schoppenhauer, Ann-Kristin; Drenkhahn, Cora M.; Ingenerf, Josef; Wiedekopf, Joshua (Studies in health technology and informatics, 2023)
To provide clinical data in distributed research architectures, a fundamental challenge involves defining and distributing suitable metadata within Metadata Repositories. Especially for structured data, data elements need to be bound against suitable terminologies; otherwise, other systems will only be able to interpret the data with complex and error-prone manual involvement. As current Metadata Repository implementations lack support for querying externally defined terminologies in FHIR terminology servers, we propose an intermediate solution that uses appropriate annotations on metadata elements to allow run-time Terminology Services mediated queries of that metadata. This allows a very clear separation of concerns between the two related systems, greatly simplifying terminological maintenance. The system performed well in a prototypical deployment.
Keywords: Metadata